Debt and credit relationships of male members of the ottoman imperial palace (1650–1700) - ARGIT, FATMA BETÜL (My University, 2022)
This research note investigates the debt-credit relationships of male members of the Ottoman imperial court, who were positioned across various departments of the imperial palace organization. It is part of a larger project called "Socio-Economic Profiles of the Members of the Ottoman Imperial Court: A Prosopographical Study (1590–1809),"1 which explores the lives of palace-affiliated people from the last years of the sixteenth century to the early years of the nineteenth. The project not only sheds light on the personal experiences of palace-affiliated people, but also reveals what it meant to be a member of the Ottoman imperial palace and allows us to trace the changing profiles of palace personnel over time. The project is based primarily on court records registered in the Evkâf-ı Hümâyun Müfettişliği (Inspectorate of Imperial Foundations) [henceforth EHM] court, one of Istanbul's shari'a courts. EHM court records offer a surprising range of information about the lives and personal experiences of male palace personnel, who occupied various positions at various levels of the Ottoman imperial palace organization. These records are important sources for reconstructing the lives of this group. These court records include material related to inheritance settlements, divorce, guardianship, slavery, waqfs, property sales, loan transactions, and other legal cases. Thus, they allow us to pinpoint the identity of their family members to whom they were married and the number of children they had, the social and professional profile of their fathers and their sons, their residential patterns, their legal heirs, their fortunes and possessions, their charitable activities, and their networks of relationships. [End Page 117] In the first 202 registers (defters), I identified 3067 male members of the imperial palace holding 375 different occupations. I have analyzed the examined group using quantitative and prosopographic methods, systematically organizing them by occupation; origins and current residential locations; identity of their fathers and mothers, grandfathers, wives and other relatives; identity of the masters of individuals of slave origin; their fathers' occupations; number of children; wealth; and location of the law court they used. The nature of the court registers does not allow us to capture all of this information for each individual, but what I can collect I process through a quantitative data analysis program (SPSS data processing software).2 While constructing the profiles of the imperial palace members, I also take into consideration their relationships with several groups. For the early modern period, EHM court records are the main source which provide the most comprehensive information regarding the nature and extent of the relationships of the group in question. These records enable us to reveal various types of relationships, including debt, credit, surety, witness, and other social relations. Existing data on the debt-credit relationships of palace-affiliated people largely reflects small-scale relationships. Therefore, instead of examining particular individuals, it is more profitable to focus on relationships of those who held certain positions within the palace organization. It is noteworthy, for example, that those who served in the positions of halberdier of the Old Palace (Saray-ı Atik teberdarı), halberdier (teberdar), and imperial gatekeeper (bevvab) appeared most often in the positions of debtor or creditor in the [End Page 118] period 1650–1700. I have examined the following questions: with whom they had debt and credit relationships, what positions they occupied in this web of relationships, and finally the extent of these relationships.
Keywords: Ottoman; Imperial court; Palace Personnel; Early Modern Era; Debt and Credit Relationships; Social Network Analysis; Gephi